Obstetric and neonatal outcome following minor trauma in pregnancy. Is hospitalization warranted?. (August 2016) - Weiner, Eran; Gluck, Ohad; Levy, Michal; Ram, Maya; Divon, Michael; Bar, Jacob; Kovo, Michal
Abstract: Objective: To evaluate if hospitalization of pregnant women, involved in minor trauma, for 24 h of surveillance, is warranted. Study Design: The medical files of pregnant women involved in minor trauma, during 2009–2014, at 22–42 gestational weeks, were reviewed. Minor trauma was defined as an injury severity score <3, no immediate complains, normal ultrasound evaluation, reactive non-stress test, and no regular contractions. Patients were divided into those who, according to our departmental protocol, were hospitalized for 24 h observation (hospitalized group), and those who refused to be hospitalized, (non-hospitalized group). Pregnancy, delivery and neonatal outcomes were compared between the groups. Results: Included in the study were 946 minor trauma patients that met the inclusion criteria. Gestational age (GA) at the trauma event was lower in the non-hospitalized group ( n  = 331) compared to the hospitalized group ( n  = 615), 29.1 vs. 30.8 weeks, p  < 0.001, respectively. There were no between-groups differences in the rate of preterm birth, vaginal bleeding, GA at delivery, or cesarean delivery. There were no cases of placental abruption or intrauterine fetal death in both groups. Neonatal outcome did not differ between the groups. Conclusion: Minor trauma during pregnancy, with normal initial assessment, is not associated with adverse pregnancy outcomes. Therefore, routine hospitalization is probably not warranted.